Turning Waste into Value: Potassium‐Promoted Red Mud as an Effective Catalyst for the Hydrogenation of CO2. Issue 11 (28th April 2020) - Russkikh, Artem; Shterk, Genrikh; Al‐Solami, Bandar H.; Fadhel, Bandar A.; Ramirez, Adrian; Gascon, Jorge
Abstract: Since 1887, red mud has been an unavoidable waste derived from the production of alumina in the Bayer process. Because of its high alkalinity and metal loading, red mud disposal and storage constitute a significant environmental risk. With worldwide storage capacity reaching its limits and no alternatives to the Bayer Process, the development of methods for the valorization of red mud is a must. In this study, red mud is converted into an efficient catalyst for the valorization of CO2 . By simple potassium promotion, 45 % conversion of CO2 with a light olefin (C2 –C4 ) selectivity of 36 % is achieved at 375 °C, 30 bar, and 9600 mL g −1  h −1, matching the performance of some of the best catalysts reported to date. Abstract : Stuck in the mud : Red mud, a waste product of alumina production, can be turned into an efficient catalyst for the valorization of CO2 into hydrocarbons by simple potassium promotion. High selectivity to C2 –C4 olefins can be achieved at high conversion levels. With a stable catalyst operation, red mud matches the performance of some of the best catalysts reported to date.